EVALUASI KEBIJAKAN PENANGGULANGAN KEMISKINAN DI KOTA METRO - Wahyu Widodo; Mirnawati, Mirnawati (Nusantara Hasana Journal, 2025)
Poverty alleviation is a top priority in regional development. Metro City, as a city in Lampung Province, has implemented various programs and policies to reduce poverty. This study aims to evaluate the effectiveness of poverty alleviation policies in Metro City using a descriptive qualitative approach. Data were obtained through in-depth interviews, field observations, and documentation of the implementation of flagship programs such as the Family Hope Program (PKH), Non-Cash Food Assistance (BPNT), and the Productive Economic Enterprise Program (UEP). The results show that although policies have been directed at reducing the burden of life for the poor, policy implementation still faces obstacles such as inaccurate targeting, limited resources, and weak coordination between agencies. Recommendations are directed at strengthening databases, ongoing monitoring, and cross-sectoral synergy.